An efficiency argument for the Basic Income Guarantee. (30th March 2006) - Widerquist, Karl; Lewis, Michael A.
This paper argues that the US welfare system needs to move away from conditionality and toward a Basic Income Guarantee (BIG). It discusses the definition of poverty and the goal of poverty policy. It critically examines five theories of the causes of poverty: the physical inability to work, single parenthood, inadequate demand for labour, inadequate human capital, and a poor work ethic. It critically discusses six policy strategies for fighting poverty: promotion of economic growth, workfare, the minimum wage, separating the 'deserving' from the 'undeserving' poor, publicly guaranteed employment, and the Basic Income Guarantee. It assesses how well each of these programmes addresses the five proposed causes of poverty, making the case that the most efficient and effective of these is the Basic Income Guarantee.